The TELERIEG Project - Erena M.; López-Francos A. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
The TELERIEG (The use of remote sensing for irrigation practice, recommendation and monitoring in the SUDOE space, www.telerieg.net), co-financed by the Interreg IVB SUDOE Programme of the European Union, has spent three years of activity with the objective of developing knowledge and tools on the application of remote sensing and geographic information systems for the improvement of irrigation water management and the response to natural risks affecting agriculture in the Southwest of Europe. The main results include an automated image processing that generates daily maps with useful parameters for irrigation management, and a geoportal adapted to the INSPIRE Directive, made up of large databases of agroclimatic and cartographic information, as well as utilities and tools based on geographic information systems and remote sensing allowing users to calculate irrigation requirements at plot scale. A collaboration network has been created of institutions working in the field of remote sensing and irrigation water management, using the most advanced techniques of high resolution images processing for estimation of agronomic parameters at field scales. All these results have been disseminated at local and international scale, covering mainly the project areas of Southwestern Europe but also other Mediterranean countries. The technologies developed by TELERIEG can contribute to improvements in optimization of the agricultural production factors mainly water.